2D-ToGo workflow: increasing feasibility and reproducibility of 2-dimensional gel electrophoresis. (July 2013) - Posch, Anton; Franz, Thomas; Hartwig, Sonja; Knebel, Birgit; Al-Hasani, Hadi; Passlack, Waltraud; Kunz, Nancy; Hinze, Yvonne; Li, Xinping; Kotzka, Jorg; Lehr, Stefan
Abstract Two-dimensional gel electrophoresis (2-DE) is one of the most powerful methods for studying global protein profiles. However, due to the multiple manual steps involved in gel based processing it is challenging to achieve the necessary overall reproducibility for a reliable comparative analysis, especially between different laboratories. To improve the 2-DE technique for quantitative analyses we have set up a robust 2-DE workflow, called 2D-ToGo, which utilizes latest innovations concerning instrumentation, consumables and protocols. Quantitative data analyses indicate the high reproducibility between replicate gels processed at a single site (intra-laboratory variation: CV 20%). The data-sets of the inter-laboratory comparison revealed similar results displaying a variation of CV 23%. The technical improvements given by our 2-DE workflow have a positive impact on process robustness and most importantly, reproducibility. Accordingly, many of the well-known challenges for resolving and quantitating up to thousands of different protein components in a given biological sample are minimized.